Task difficulty modulates the effect of eye contact on word memory in females - Xinghe Feng; Qiqi Hu; Chaoxiong Ye; Zhonghua Hu (BMC Psychology)
Abstract Background The influence of eye contact on memory has been a topic of extensive study, yet its effects remain ambiguous. This inconsistency may be attributed to the varying levels of task difficulty encountered when conducting this type of research. Methods To explore this possibility, our study used a word memory task that also integrated eye gaze as a means of examining how task difficulty (easy or difficult) modulates the effect of eye contact on word memory. A total of 41 participants engaged in the memory task under varying eye contact conditions. Results Our findings revealed a significant interaction between task difficulty and eye contact: For easy tasks, memory accuracy was lower with eye contact, whereas for difficult tasks, accuracy was improved with eye contact. Intriguingly, this effect was predominantly observed in female participants. In easy tasks, eye contact appeared to hinder memory performance in females, whereas it enhanced performance in difficult tasks. Conclusions These results suggest that the impact of eye contact on memory is not uniformly positive or negative, but is instead contingent on task complexity and influenced by gender differences. This study contributes new insights into the fluctuating effects of eye contact on memory, thereby enriching our understanding of the relationship between nonverbal social cues and cognitive processes.